THE PROCESS OF MAKING THE LASEM BATIK MODULE BOOK - Pratiwi Kusumowardhani; Syafira Sukma Maharani (UPT Pusat Penerbitan LP2MPP ISI Bali, 2022)
Batik Lasem is one of the batiks that have a characteristic that Batik Lasem is very famous for because of its characteristics as a beautiful coastal batik with bold coloring so that the batik made has a high selling value. In the field study, it was found that the development of fashion design on lasem batik was minimal due to the lack of reference books and technical training in making fashion designs. In writing this time, the author wants to make a unique module book for lasem batik fashion design. The method used is the method of writing in two stages, namely the stage of qualitative method, qualitative field study (Field Study), and the second stage, namely the stage of the design production process and book layout with a focus on three stages of the process in making book designs, namely the pre-production process, production, and post-production. ThisThis discussion is limited to the first stage, namely the qualitative stage, the type of qualitative field study. The purpose of making this paper is to answer requests from craftsmen to present a design module book for the stages of making fashion clothing designs, especially the Batik Lasem design.